Effect of monocular sensitivity on binocular summation of luminance-modulated flicker. - C Vijay Reena Durai; Amithavikram R Hathibelagal; Marisa Rodriguez-Carmona; John L Barbur; Shrikant R Bharadwaj (PLoS ONE, 2023)
Binocular summation of luminance contrast signals in the spatial domain has been investigated in many studies, but less attention has been paid to the analogous interactions in the temporal domain. The present study determined the impact of monocular sensitivity on the binocular detection of luminance-modulated flickering stimuli. Binocular summation ratios (BSRs) were determined in 13 visually-normal adults for a range of monocular flicker modulation thresholds (FMTs), generated by changing stimulus size (7'- 60') and luminance (mesopic and photopic). Monocular and binocular FMTs were measured at the point of regard and in each of the four quadrants at 5° eccentricity for each target size and luminance using the Flicker-Plus test. Monocular and binocular FMT's increased with decreasing target size for all retinal locations (p<0.001), and were overall larger for mesopic than for photopic condition (p<0.001). BSRs for mesopic (mean±SD: 1.50±0.21) and photopic (1.60±0.24) stimuli were greater than unity (p<0.001), with the latter showing larger estimates than former (p<0.001). BSRs showed no significant trend across target sizes for both luminance conditions (p>0.12). The results demonstrate that the visual system successfully summates inputs from the two eyes to enhance flicker detection, independent of their absolute monocular detection thresholds. These findings may serve as a predictive baseline for further experiments designed to determine how other stimulus properties and interocular differences in monocular thresholds may affect the binocular perception of flicker.